A study of cytology and colposcopy in VIA (visual inspection of cervix with 5% acetic acid) positive women - Arora, Ruchi S.; Patel, Shilpa M.; Poddar, Pabashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cervical cancer is the most common cancer among Indian women. Cervical cancer is preventable in pre-invasive state when effective programmes are implemented to detect and treat its precursor lesions. "Single Visit" screen and treat strategy that uses VIA and colposcopy alone that eliminates the need for repeated visits due to delays in diagnostic results, will be highly attractive in terms of cost effectiveness and compliance to treatment, which is crucial to bring down the incidence and mortality due to cervical cancer. The present study evaluates the performance of colposcopy vs conventional cytology in estimating the presence and grade of cervical disease against the reference standard of histopathology as a secondary test modality to triage women found positive on primary screening by visual inspection with 5% acetic acid (VIA). Methods: This is a retrospective study carried out on 50 women aged between 18-50 years who tested positive on VIA between August 2013 to November 2015. Data were entered in the institution using standard computer software [EPIINFO software]. Diagnostic accuracy for single test was calculated using 2*2 tables and standard formulae. Results: The diagnostic accuracy of Pap smear was found to be 77% and that of Colposcopy was 87%. The accuracy of colposcopy was higher than that of Pap smear. Conclusions: Invasive cervical cancer is preceded by pre-invasive disease in most women. There is a lag time of 10-20 years before the disease progresses from pre-invasive to invasive disease. Prevention of invasive cancer is by screening, diagnosis and treatment of pre-invasive diseases. Thus, early diagnosis of CIN (cervical intraepithelial neoplasia) in adult women is a desirable goal.